An analytical study of optimal roller intermeshes for the plate leveling process. (January 2021) - Liu, Zhifang; Luo, Yuanxin; Wang, Yongqin; Warren Liao, Thunshun; Deng, Ming
Leveling process is usually used to minimize the plate defects including flatness imperfections and uniformity of internal stress in the plate industry. Roller intermeshes are important parameters in the leveling process to ensure the high-quality leveled plate. Some current researches treat the plate as a simple beam and ignore the stress superimposed effect to study how to set the roller intermeshes. This article presents an analytical optimization model to search the optimal entry and exit intermeshes for each incoming plate with consideration of the relationship between the roller intermeshes and bending curvatures during the whole leveling process. The optimization model was solved and the results were verified with production data. The relationship between the optimal roller intermeshes and plate thickness, yield stress, and Young's modulus were discussed in details. It was found out that the roller intermeshes can be set the same for different incoming plates but with equal elastic limit curvature. A four-dimensional database of optimal roller intermeshes about different elastic limit curvature, expected plastic strain ratios, and roller spaces was built. The roller intermeshes can be quickly tracked in less than 1 s as long as the thickness, yield stress, and Young's modulus of incoming plate and roller space are given according to the database so that it can be used effectively on the leveling production line.